Telehealth use in primary healthcare collaborative interprofessional practice: protocol for a scoping review - Marina Peduzzi; Gisele Silvestre Belber; Raíssa Ottes Vasconcelos; Heloise Lima Fernandes Agreli; Ana Estela Haddad; Valéria Marli Leonello (BMJ Open)
Introduction Telehealth is a growing topic, with potential to improve access to primary healthcare. However, there is a lack of knowledge regarding how telehealth could facilitate interprofessional collaboration that is recommended to strengthen the comprehensive approach of primary healthcare. The objective is to identify the characteristics and applications of telehealth services related to the interprofessional collaborative practice of primary healthcare professionals.Methods and analysis This review will cover studies including as target population those health professionals who work in telehealth services; as concept, telehealth in relation to collaborative interprofessional practice; and as context, primary healthcare. A scoping review will be carried out according to the Joanna Briggs Institute methodology. Databases to be searched include MEDLINE, CINAHL, Embase, Eric, Scopus, LILACS and Web of Science. All identified records will be grouped, duplicates will be removed, titles and abstracts will be selected by two independent reviewers, and the full text of selected articles will be evaluated in detail. A data extraction tool developed by the reviewers will be used for data extraction. The results will be presented in data map format in a logical way, in a diagram or in a tabular format, accompanied by a descriptive summary.Ethics and dissemination No ethical approval is required for this study. A manuscript based on this scoping review will be submitted to a journal and we hope it will contribute to scientific knowledge on the interprofessional field and key research findings will be sent to key events on interprofessional practice and education.Systematic review registration This scoping review was registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/2BV8D).